(untitled) (Research, Society and Development, 2022)
Objective: to evaluate the product of nursing care in a public university hospital. Method: cross-sectional epidemiological study, carried out in a university hospital in the northern region of the State of Paraná, Brazil. Nursing care was assessed and classified according to the Nursing Care Product Assessment scale. Results: 173 evaluations of the nursing care product were obtained, carried out by 62 nurses. The nursing care product was classified as “good” in the institution. Group two (adult intensive care) had the highest score in the care rating while group one (adult inpatient units) had the lowest score. The most critical assessments were “interaction and multidisciplinary action” and “resources needed to provide care”. The best classification was attributed to the item “planning nursing care”. Conclusion: the instrument proved to be a relevant strategy for identifying the critical factors that impact the production of nursing care in a multicausal model.